An inside view on Blended Learning: The relationship between blended learning and service quality / Norida Abu Bakar...[et al.] - Abu Bakar, Norida; Ahmad Ridzuan, Ahmad Nur Azam; Md Jelas, Imran; Zulkifli, Faiz; Jahya, Arnida; Luaran, Johan Eddy (2014)
The purpose of this paper is to review the application and the development of blended learning from the student perspective. Blended learning combines both the classroom and technology to engage learners in meaningful learning experiences, has led to new teaching models and learning styles that embraces the latest technology.As the number of the student intake are growing, it is important to the university to identify the level of saticfaction on Blended learning. The paper use quantitative research methodology to answer the three research questions of this study. Both descriptive and inferential statistics were used. Data collected was sorted, classified, coded and tabulated for an ease of analysis by using student statistical package SPSS 20.The result shows only two variable are significant to the blended learning. The conclusion shows the topic on blended learning was good because in the developmental stage and it needs effective improvement from the organization in terms of infrastructure and training of instructors and learners with efficient skills in teaching and learning online.